Neuroendocrine Tumors of the Ampulla of Vater: Presentation, Pathology and Prognosis - Jayant, Mayank; Punia, Rajpal; Kaushik, Robin; Sharma, Rajeev; Sachdev, Atul; Nadkarni, Nikhil K; Attri, Ashok (JOP. Journal of the Pancreas, 2012)
Context Neuroendocrine tumors of the pancreatic ampulla are uncommon. The final diagnosis is based on histology, and at times, it may be difficult to diagnose them pre-operatively since they present with a similar clinical picture to adenocarcinomas of this region. Objective To identify neuroendocrine tumors of the ampulla, as well as their presentation and management. Design A retrospective review of patients treated at a tertiary care institute was performed over a six-year period from 2005 to 2010. Patients Cases with periampullary cancers were investigated. Main outcome measures The case records were scrutinised for the clinical presentation, management and outcomes. Results A total of 4 cases (7.7%) of neuroendocrine tumors of the ampulla were identified from 52 patients with periampullary lesions, at a mean age of presentation of 49 years. The common mode of presentation was progressive jaundice (3 of 4 patients); pancreaticoduodenectomy was performed in 3 patients. One patient underwent palliative endoscopic stenting for metastatic disease. On histopathology, 2 of the patients had poorly differentiated (neuro)endocrine carcinoma (high grade), and 2 had well differentiated (neuro)endocrine carcinoma (1 low grade and 1 intermediate). All the tumors stained positively with chromogranin A. The patients who underwent pancreaticoduodenectomy are on regular follow-up and remain free of disease. Conclusions Neuroendocrine tumors of the ampulla are distinct entities presenting clinically with jaundice. They stain positive with chromogranin A on histopathology. Pancreaticoduodenectomy should be performed as it is associated with good outcome.